Analysis of pharmacological and non-pharmacological treatment in joint hypermobility sysndrome (jhs) from 2017 to 2021: A systematic review - Takahashi-Ferrer, Carolina Mayo (2022)
Objectives: To analyze non-pharmacological and pharmacological treatments in patients with joint hypermobility syndrome (JHS). Methods: It is a systematic review of research papers, where the PRISMA recommendation was followed looking for scientific articles published in Redalyc, Eric, Sciencedirect, Latindex, Scopus, Alicia, Elsevier, Pubmed, LILACS, SciELO, EBSCO, and Google Scholar, during the period 2017 to 2021. Results: From the initial total of 261 019 studies corresponding to the search, without applying filters, four articles were selected, all of which describe non-pharmacological treatments considering physical therapy as the most adequate and effective alternative to strengthen and re-educate the joints, in order to reduce pain temporarily. You should not overexert yourself and you should respect the limitations of each patient; otherwise, it would be detrimental to health. On the other hand, a single study of those mentioned, details pharmacological treatments recommending amitriptyline and fluoxetine as the option to mitigate chronic pain, in the presence of pain crisis paracetamol is recommended, however, it is emphasized that the use of Non-steroidal anti-inflammatory drugs (NSAIDs) and opiates since they could also be used for acute pain, but they are not recommended because they are not well tolerated by these patients due to the fragility of their tissues due to the alteration in the collagen level they present. Conclusions: There have been no significant advances in the last five years with respect to treatments for patients with JHS compared to past years. There is more evidence on physical therapy to treat the ailments and symptoms of these patients compared to the drug options that can be used to mitigate pain and reduce symptoms.